McIndoe Vaginoplasty in MRKHS: Case Report and Literature Review - Newton Ashish Shah; Manish Yadav; Suman Verma; Digraj Yadav; Aalok Kumar Yadav; Asmita Ghimire; Hima Rijal; Poonam Koirala (Clinical Case Reports)
ABSTRACT Mayer–Rokitansky–Küster–Hauser syndrome (MRKHS) is a rare congenital disorder characterized by agenesis of the uterus and upper two‐thirds of the vagina. It affects around 1 in 4000–5000 females and is of two types: type 1, also known as isolated Müllerian aplasia or Rokitansky, which involves only uterovaginal agenesis, and type 2, presents as uterovaginal agenesis along with renal, cardiac, and other organ anomalies. Despite the absence of vaginal and uterine structures, individuals with MRKHS typically present with normal secondary sexual characteristics and ovarian functions. A 26‐year‐old female presented with primary amenorrhea. Despite this, she had typical secondary sexual characteristics. Physical examination revealed normal pubic hair distribution and external genitalia, consistent with Tanner's stage 5 development. Further evaluation via magnetic resonance imaging (MRI) confirmed diagnosis of MRKHS type II, revealing the absence of the uterus and upper two‐thirds of the vagina, with normal ovaries and absent left kidney. A multidisciplinary team performed McIndoe vaginoplasty creating a successful neovagina, measuring 7 cm in length, using split‐thickness skin graft. MRKHS, a rare congenital anomaly involving Müllerian duct abnormalities, poses diagnostic and therapeutic challenges. The etiology remains unknown, but it likely stems from defective Müllerian fusion during embryologic development. Differential diagnosis from conditions like androgen insensitivity syndrome (AIS) is crucial. MRI is important in diagnosis, revealing associated anomalies. Treatment aims to restore sexual function. This case presents that MRKHS can occur with normal hormonal function and typical secondary sexual characteristics. Neovagina creation is an effective surgical intervention for young females seeking to restore sexual function.